Company--community partnership outgrower schemes in forestry plantations in Indonesia: an alternative to conventional rehabilitation programmes - Nawir, A.A.; Gumartini, T. (Food and Agriculture Organization of the United Nations, 2003)
Indonesia has a considerable area of degraded land requiring rehabilitation. However, most rehabilitation projects in the past have been government driven, depending on public funding (ndonesian government and international donors), and have focused mainly on technical aspects. As a result people living in surrounding targeted areas are not adopting rehabilitation techniques. Innovative approcahes are necessary if the objectives of a rehabilitation programme are to be met while providing benefits to private companies and local people. The findings of a study of outgrower schemes in Indonesian timber plantations suggested that company--community partnerships could be an alternative for implementing rehabilitation programmes. The partnership arrangement over a 10- to 45- year period is based on a contract. It states the rights and duties of each party in establishing a forestry plantation and the benefit-sharing agreement at the time of harvest. The schemes take place on logged-over forests and idle lands, mostly Imperata grasslands. The partnership provides opportunities for forestry plantation companies to play a social role and rehabilitate degraded resources. It also provides job opportunities to local people and incomes from harvested timber at the end of each rotation under a long-term contract.